Assessing the Feasibility of Vertical Farming as a Sustainable Solution to Food Production - Al-Farouni Mohammed; Hussein Abbas Hameed Abdul; Ravinder Rathod (SHS Web of Conferences)
The current global food production system faces significant challenges, including limited land availability, fluctuating temperatures, and inefficient supply chains. Traditional farming methods are becoming obsolete and need a solution that we can refer to as innovative solutions to support the rising demand for food. These problems are only exacerbated by the expansion of urban areas and the loss of arable land. A promising alternative is vertical farming, which involves cultivating crops in stacked layers within controlled environments. It is based on the idea that vertical farming is feasible by examining the efficiency, resource utilization, and productivity of different types of vertical farms. The system combines the most advanced cultivation technologies in aquaponics on one side and hydroponics and aeroponics on the other, to improve resource efficiency and increase crops. These techniques allow vertical farming to have minimal water usage, use less land, and have a stable climate for year-round crop growth. The discovery shows that vertical farming can extensively increase agricultural output and conserve water and land resources. The results bring about the conclusion that future food production could be solved by vertical farming overcoming today's problems of agricultural practices.